The inequality effects of a dual income tax system - Peter J. Lambert; Thor O. Thoresen (Statistics Norway, Research Department, 2011)
The overall inequality effects of a dual income tax (DIT) system, combining progressive taxation of labor income with proportional taxation of income from capital, are investigated. Simple examples show that correlations between distributions of wage and capital income, the degree of tax rate differentiation in the DIT, and reranking of tax-payers can be expected to complicate the analysis. We trace out what can be said definitively, obtaining sufficient conditions for unambiguous inequality reduction and identifying the nature of the implicit redistribution between labor and capital income which is involved, with the help of Norwegian income tax data.
Keywords: D31; D63; H31; 330; Personal income tax; dual income tax; redistributive effect